Noncoding RNAs in pyroptosis and cancer progression: Effect, mechanism, and clinical application - Zhang, Menghui; Dang, Pengyuan; Liu, Yang; Qiao, Bingbing; Sun, Zhenqiang (Frontiers in Immunology, 2022)
Cell death is generally classified into two categories: regulated cell death (RCD) and accidental cell death (ACD). In particular, RCD is a kind of genetically controlled process, including programmed apoptotic death and programmed necrotic death. Pyroptosis, an inflammatory form of programmed necrotic death, causes inflammation in cells. The influence of pyroptosis on tumor is complicated. On the one hand, pyroptosis triggers antitumor response. On the other hand, pyroptosis may induce carcinogenesis. Pyroptosis is initiated by various factors, especially non-coding RNAs. In this review, we discuss the effects of ncRNAs on pyroptosis and the mechanisms by which ncRNAs initiate pyroptosis. Moreover, we introduce the influence of ncRNA on tumor resistance via pyroptosis. Additionally, we summarize how ncRNA-associated pyroptosis modulates the tumor microenvironment (TME) and thereafter triggers antitumor immune response. Finally, pyroptosis-related ncRNAs are promising diagnostic and immunotherapeutic biomarkers and therapeutic targets